2005
DOI: 10.1108/00368790510601707
|View full text |Cite
|
Sign up to set email alerts
|

Abrasive wear behaviour of concussor jaws welded using a gas metal arc welding process

Abstract: Purpose -The aim of the research is to investigate the influence of gas metal arc welding on the wear performance of worn concussor jaws. Design/methodology/approach -Worn parts were welded using the gas metal arc welding process. Various wires were used for this purpose. These welded parts were subjected to wear tests under different loads, and changes in the hardness and microstructures were examined. A pin-on-disc wear test apparatus was used. Findings -As a result of this study, the following findings are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The reason of the slowness in total weight loss is caused by the work hardening during the abrasion. The presented results are consistent with the earlier works [10,18].…”
Section: Abrasion Resistancesupporting
confidence: 83%
“…The reason of the slowness in total weight loss is caused by the work hardening during the abrasion. The presented results are consistent with the earlier works [10,18].…”
Section: Abrasion Resistancesupporting
confidence: 83%
“…In our tests, it was accepted that wear resistance changes depending on hardness; in other words, as hardness increases, so does wear resistance, and therefore, wear resistance depends mostly on hardness (Gü lenç and Kahraman, 2003;Kıratlı, 2005;Hurricks, 1974). According to the optical microscope images, it was observed that as boronizing duration and temperature increased, thicker boride layer was obtained.…”
Section: Hardness and Microstructure Resultsmentioning
confidence: 68%